STRATEGI SEGMENTASI PASAR, PENENTUAN TARGET KONSUMEN, DAN POSISI MEREK DALAM MENINGKATKAN EFEKTIVITAS PEMASARAN: KAJIAN PUSTAKA - Tehedi Tehedi; Wagiyo Wagiyo (JIEKA: Jurnal Integrasi Ekonomi, Keuangan, dan Akuntansi, 2025)
This study analyses the strategic role of market segmentation, consumer targeting, and brand positioning within the STP framework to enhance marketing effectiveness amid Indonesia's competitive and rapidly digitalising market dynamics, where segmentation enables the division of a heterogeneous market into homogeneous segments based on geographic, demographic, psychographic, and behavioural criteria, targeting selects viable segments through measurability, accessibility, substantiality, and actionability with an undifferentiated to micromarketing approach, while positioning creates a unique perception through value proposition attributes, benefits, users, competitors, or quality-price based, so that the synergy of the three results in a 20-40% increase in marketing ROI, cost efficiency, consumer loyalty, and competitive advantage for MSMEs and large companies. The research method used is a literature review, adopting reputable national and international books and journals. The main findings confirm STP as a fundamental enhancer of holistic marketing effectiveness, with theoretical implications that enrich strategic marketing literature and provide practical, actionable guidance for practitioners, as well as recommendations for future empirical testing using mixed methods and AI integration for ASEAN generalisation.